The psychologist in RSA: Development of an intervention competence within the residential and healthcare context of care for the elderly - Bolli, Lorenzo (Quaderni di Psicologia Clinica, 2023)
With this contribution I want to share the developments occurred during my work as a psychologist in a RSA (nursing home), referring to some interventions that I have conducted. It is possible to identify a line of development within their succession, inherent in the construction of the competence to deal with the specific problems encountered in working with the third and fourth age, in the context of organizations that respond to the demand for care and assistance of elderly people in various ways no longer self-sufficient. Building these skills has not been without its challenges. On the contrary, it proceeded from recognizing how even the psychologist's action, coherently with the culture of a context in which the elderly person rarely speaks, may not be aware of his/her existence. The work of the psychologist runs the risk of eluding the elderly, silencing their presence. The alternative lies in admitting the survival and irreducible vitality of his unconscious emotions; this makes possible to discover their expectations when entering the new life condition and staying in the RSA. In this discussion, I propose the hypothesis that the definition of a peculiar identity of the elderly, different from what is foreseen by the evolutionary schemes prescribed by a life cycle psychology, contributes to the construction of a psychological function. Function that identifies specific intervention requests in the residential context of care for the elderly, and which was able to develop within a specialization course in psychoanalytic psychotherapy.
Keywords: psychological function in RSA; dementia; assistance to the elderly; emotional life of the elderly; counseling for the elderly's family.